The Concept of 'Aqal in the Al-Qur'an - Adib Fattah Suntoro; Amir Sahidin (Tasfiyah: Jurnal Pemikiran Islam, 2021)
Discourse on the meaning of 'aqal is not as simple as it seems. The commonly translated 'aqal' pronunciation of "reason" does not actually fully represent the meaning intended by the original word. Because the word ‘akal’  in Indonesian is only related to intellectual activity or rational reasoning. This certainly results in a narrowing of the meaning of 'aqal itself. Therefore, this paper seeks to devise the concept of 'aqal in the Qur'an. Through the analytical-descriptive study of authoritative literature, It is found that in interpreting the 49 verses related to 'aqal the mufasir can not be separated from three contexts of discussion: about the universe or the power of Allah; about the infidels or opponents of Islam; And about the Kitab or Qur'an. On the basis of understanding the above verses, mufasir defines reason terminologically by summarizing it into two great terminology, related to rububiyyah and the uluhiyyah of Allah. In addition, to complete the meaning of 'aqal in the Qur'an, this article will also mention the views of philosophers, mutakallim and theologians, So it is increasingly seen that the meaning of 'aqal is not as simple as it is often translated with ‘akal’. Based on this study, it can be justified that the word 'aqal which Allah uses in the Qur'an contains a broad concept.